2019
DOI: 10.1590/1980-0037.2019v21e59832
|View full text |Cite
|
Sign up to set email alerts
|

Sports potential modeling of young basketball players: a preliminary analysis

Abstract: The aims of this study were: 1) to evaluate the sports potential of young basketball players; 2) to identify variables that discriminate sports potential assessed by coaches; 3) to verifythe relationship between classification of the multidimensional profile of athletes and classification of the sports potential by coaches. Sixty-two young basketball players aged 15.6±1.1 years from U-15 (n = 24) and U-17 (n = 38) categories participated in the study. A test battery was applied to evaluate sports potential ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…The model observed a higher probability of reaching the NBB in athletes with the following characteristic combination: chronologically younger and taller, who play for clubs in the southeast region, are selected for the first time to play U22, not playing U15 national championship, have been re-selected to play the youth national basketball championships, and over time have changed playing position, club, and region. The current understanding is that multidisciplinary and dynamic approach must be used to assess sport potential (Ribeiro Júnior et al, 2019 ) and development (Sáenz-López et al, 2005 ) of young basketball players. Talent development and expertise must be taken into account with a wide range of factors (Gulbin et al, 2013 ; Hambrick et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model observed a higher probability of reaching the NBB in athletes with the following characteristic combination: chronologically younger and taller, who play for clubs in the southeast region, are selected for the first time to play U22, not playing U15 national championship, have been re-selected to play the youth national basketball championships, and over time have changed playing position, club, and region. The current understanding is that multidisciplinary and dynamic approach must be used to assess sport potential (Ribeiro Júnior et al, 2019 ) and development (Sáenz-López et al, 2005 ) of young basketball players. Talent development and expertise must be taken into account with a wide range of factors (Gulbin et al, 2013 ; Hambrick et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In cross-sectional and short-term longitudinal studies, stature (Zarić et al, 2020 ), birthdate (Torres-Unda et al, 2013 ; Rubajczyk et al, 2017 ), maturation (Arede et al, 2019 ), physical fitness (Hoffman et al, 1996 ; Hoare, 2000 ), and skills (Arede et al, 2019 ) can be useful to predict individual performance and the selection of young basketball athletes. Thus, a more holistic and ecological analysis is considered an advance in the talent identification and development process to provide additional insight in the sport potential of the players (Moxley and Towne, 2015 ; Ribeiro Júnior et al, 2019 ). Hence, young athletes who present the right combination of characteristics required for good performance in basketball will probably have a greater chance of success.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the dribbling deficit provides a more isolated measure of dribbling speed than tests using total performance times (Scanlan et al, 2018) However, it has been mentioned how important it is to involve the coach in TID too. In this regard, (Junior, Vianna, Lauria, Coelho, & Werneck, 2019) reported that coach evaluation is essential and should be part of the TID process. Coaches' performance during years of training can influence TID due to the time spent and the environment involving the player (Roberts et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the PE teachers evaluated their students on the intangible aspects of sporting potential and the expectation of future success (Chart 1). The indicators of sporting potential evaluated, as well as the procedures for the tests, and measurements are described in Miranda et al (2019), 52 Ribeiro Júnior et al (2019) 53 and Werneck et al (2020). 24 The battery of tests was applied during the students' physical education class time, lasting approximately 90 minutes, on three different days.…”
Section: Instruments and Proceduresmentioning
confidence: 99%